Self-Efficacy of Patients with Type 2 Diabetes Mellitus Who Consume Herbs - Anita Joeliantina (Health Notions, 2021)
Diabetes mellitus (DM) is a chronic disease with metabolic disorders characterized by hyperglycemia that can cause it. Self-efficacy is a factor that contributes to preventing complications. This study aims to explore self-efficacy in managing blood sugar levels in patients with DM. This study was a cross sectional study, with a sample size of 125 T2DM patients who used herbs and carried out controls to the public health center in Surabaya. The instrument used for data collection was a questionnaire. The data analysis used was descriptive analysis and Spearman analysis. The self-efficacy value obtained was 52% having low self-efficacy. Patients with DM, had a low self-efficacy regarding dietary management (59.2%) and the use of herbs as a complement to treatment was high (80%). There was a relationship between self-efficacy of eating management, physical activity, and herbal use with random blood sugar levels, with p-values of 0.017, 0.023, and 0.040, respectively. Self-efficacy is an important part that can support the success of T2DM patients in managing blood sugar levels. T2DM patients who use herbs have low self-efficacy, which has the potential to reduce self-care behavior. Nurses must support patients in self-care by paying attention to patient self-efficacy. Keywords: self-efficacy; diabetes mellitus; use of herbs